A case study analysis : Sapura Telecommunications Berhad Sapura Telecommunications Berhad / Atma Suria Mokhtar … [et al.] - Mokhtar, Atma Suria (Faculty of Accountancy, 2001)
This case study is about the analysis of strategic management for Sapura Telecommunication Berhad also done in partial fulfillment of Strategic Management (MGT 585). The case study was completed by doing the entire analysis requirement with the help of the secondary sources such as newspapers article, magazines, annual report, and information on Internet. Sapura Telecommunication Berhad (STB) is one of the successful subsidiaries of Sapura Group Berhad. STB are listed on KLSE Main Board (Technology) and before this the company knows as Rilla Holding Sdn Bhd and had been change to Sapura Telecommunication Berhad on 12.4.90 and to present form on conversion.